THE SIGNIFICANCE AND CONNECTION OF THE PRINCIPLES OF CONSTITUTIONALITY AND LEGALITY WITH THE LEGAL ORDER AND RULE OF LAW - Dejan Logarušić; Milan Rapajić (Pravo, 2025)
The rule of law is one of the oldest and most significant ideas in the history of legal and political thought. Contemporary legal scholars widely emphasize that this concept occupies a central place in clearly articulated views concerning the state, law, politics, and economics. As an ideal worth striving toward, the rule of law has been addressed by leading figures in law, economics, and political theory. The discourse on the principles of constitutionality and legality has consistently served as a cornerstone in affirming the importance of the rule of law in modern legal systems. This is particularly relevant given that these principles are essential to the existence of the legal state. In accordance with the focus of this paper, the authors analyze several key issues: how to determine the significance of the relationship between the principles of constitutionality and legality and the rule of law, how to conceptually present the essence of constitutionality, legality, the rule of law, and the legal state.